Sinergi Pendidikan, Pemasaran Digital dan UMKM Sebagai Upaya dalam Mengembangkan Potensi Desa Rajamandala - Yugi Hilmi; Marni Marni; M Rifcky Adamsyah; Herawati Hasna; Indri Lestari; Ace Abdul Kholik; Nurhalimah Nurhalimah (Universitas 45 Surabaya, 2025)
Real Work Lecture (KKN) is a form of student service to the community that aims to implement science directly in the village environment. This KKN activity was carried out in Rajamandala Village, Rajapolah District, Tasikmalaya Regency with a focus on education and economy. In the field of education, students carry out waste processing activities into simple works aimed at students of SD Negeri 3 Rajapolah. This activity aims to increase environmental awareness from an early age and foster students' creativity in utilizing waste into products with useful value. Through educational approaches and hands-on practice, students are encouraged to care more about the surrounding environment. Meanwhile, in the economic sector, students held a digital marketing and financial management workshop for Micro, Small, and Medium Enterprises (MSMEs) in Rajamandala Village. This activity aims to increase MSME actors' understanding of online marketing strategies and effective financial management to support business sustainability. The KKN programs that have been implemented are expected to have a positive impact, increase the capacity of human resources, and contribute to the sustainable development and independence of Rajamandala Village.